1982
DOI: 10.1177/00220345820610071001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supragingival Plaque Control on the Composition of the Subgingival Microbial Flora in Ligature-induced Periodontitis in the Monkey

Abstract: The influence of supragingival plaque control on the subgingival microflora and clinical parameters of ligature-induced periodontitis in the Cynomolgus monkey was investigated. No clinical changes were observed during the six-week experimental period. The total cultivable flora and the proportions of total black-pigmented Bacteroides (BPB) and asaccharolytic black-pigmented Bacteroides decreased significantly in the cleaned test sites as compared to those in the non-cleaned controls. The study suggests that si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 41 publications
1
21
1
Order By: Relevance
“…Although few previous studies have also shown associations between supragingival plaque and subgingival flora, 7‐12 the unique contribution of this study is that it suggests that the behavior of certain subgingival microorganisms may be influenced by supragingival plaque levels. At low supragingival plaque levels, only Pg was significantly associated with increased risk of CAL.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although few previous studies have also shown associations between supragingival plaque and subgingival flora, 7‐12 the unique contribution of this study is that it suggests that the behavior of certain subgingival microorganisms may be influenced by supragingival plaque levels. At low supragingival plaque levels, only Pg was significantly associated with increased risk of CAL.…”
Section: Discussionmentioning
confidence: 69%
“…It has long been recognized that the removal of supragingival plaque leads to a decrease in gingivitis. What is less appreciated, however, is the effect of supragingival plaque on periodontitis even though few studies have shown that the composition of subgingival flora is influenced extensively by supragingival plaque and that the removal of supragingival plaque alone leads to reduced subgingival bacterial counts 7‐12 …”
mentioning
confidence: 99%
“…brushes was used. GJERMO & FLOTTRA (5) found interdental As shown by SIEGRIST & KORNMAN (8) brushes to be superior to toothpicks and supragingival cleansing in monkeys results in dental floss comparing their plaque-removal a significant decrease in the proportions of in interproximal spaces where the papilla total cultivable flora and total black pigwas missing. NAYAK & WADE (6) came to the mented Bacteroides and asaccharolytic black pigmented Bacteroides subgingivally.…”
mentioning
confidence: 94%
“…We and others have shown that characteristics of the innate and humoral immune responses and the destruction of bone and connective tissue that accompany naturally occurring and ligature-induced periodontitis in Macaca fascicularis, Saimiri sciureus, Macaca nemestrina, Macaca mulatta, and Papio anubis parallel those observed in human periodontitis (5,6,(21)(22)(23). Nonhuman primate periodontal pockets are a habitat for a complex microbiota (18,20,(24)(25)(26)(27)(28) consisting of Gram-negative anaerobic species, such as Porphyromonas gingivalis (29)(30)(31), Treponema denticola (29,32,33), and Tannerella forsythia (29,34,35), similar to the microbial complexes identified in the subgingival biofilms of humans (36,37). Thus, there appears to be a relationship between the microbiological and immunological studies of gingivitis and periodontitis in humans and those which have been described for periodontitis in nonhuman primates.…”
mentioning
confidence: 99%